DIGITALISASI DONGENG NUSANTARA SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN ERA DIGITAL DI TINGKAT SEKOLAH DASAR - Agusta Kurniati; Ursula Dwi Oktaviani; Thomas Joni Verawanto Aristo (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2022)
This study aimed to: Produce Digital Learning Media in Indonesian language learning, know the feasibility of Digital Learning Media as an alternative media used in learning Indonesian, knowing the opinions of C11 PGSD students as designers and users in the field. This research uses the research and development (R&D) type. This development research is a research method used to produce a certain product and will also be tested for the effectiveness and attractiveness of the product. The model used in this study is the ADDIE model by Robert Maribe Branch. This model aims to produce new products through several stages of development which include the stages of analysis, design, development, implementation and evaluation. The subjects in this study were 35 students of the C11 PGSD Study Program. This study's methods of data collection were observation, interviews, and questionnaires. The research instruments were in the form of observation guides, interview guides, and questionnaires. The research results were the design of the Digital Nusantara Fairy Tale Media, which media experts had tested, material experts, and students as product users. The field states that Digital Fairy tales are suitable for use with 90% media expert test results, material expert test 85%, small scale test 80%, and large scale 85%. The results concluded that the Digital Nusantara Fairy Tale is feasible to be used as an alternative learning media at the elementary school level.